Cancer cell genetics shaping of the tumor microenvironment reveals myeloid cell-centric exploitable vulnerabilities in hepatocellular carcinoma - Ramirez, Christel FA; Taranto, Daniel; Ando-Kuri, Masami; de Groot, Marnix HP; Tsouri, Efi; Huang, Zhijie; de Groot, Daniel; Kluin, Roelof JC; Kloosterman, Daan J; Verheij, Joanne; Xu, Jing; Vegna, Serena; et al. (bioRxiv, 2023)
Myeloid cells are abundant and plastic immune cell subsets in the liver, to which pro-tumorigenic, inflammatory and immunosuppressive roles have been assigned in the course of tumorigenesis. Yet several aspects underlying their dynamic alterations in hepatocellular carcinoma (HCC) progression remain elusive, including the impact of distinct genetic mutations in shaping a cancer-permissive tumor microenvironment (TME). Here, we generated somatic HCC mouse models bearing clinically-relevant oncogenic driver combinations and subsequent pathway activation that faithfully recapitulated different human HCC subclasses. We identified cancer genetics’ specific and stage-dependent alterations of the liver TME associated with distinct histopathological and malignant HCC features. These models ranged from T cell-rich, more indolent HCC to aggressive tumors exhibiting heightened myeloid cell infiltration. Interestingly, MAPK-activated, NrasG12D-driven tumors presented a mixed phenotype of prominent inflammation and immunosuppression in a T cell-excluded TME, contrasting with NrasG12V HCC, enriched in adaptive immune cells. Mechanistically, we identified a NrasG12D cancer cell-driven, MEK-ERK1/2-SP1-dependent GM-CSF secretion enabling the accumulation of immunosuppressive and proinflammatory monocyte-derived Ly6Clow cells. GM-CSF blockade curbed the accumulation of this myeloid cell subset, reduced inflammation, induced cancer cell death and prolonged animal survival. Furthermore, the anti-tumor effect of GM-CSF neutralization synergized with the clinically-approved inhibition of the vascular endothelial growth factor (VEGF) to inhibit HCC outgrowth. These findings underscore the striking alterations of the myeloid TME consequential to MAPK pathway activation intensity and the potential of GM-CSF inhibition as a myeloid-centric therapy tailored to subsets of HCC patients.